Normative values of the Brief Repeatable Battery of Neuropsychological Tests in a Brazilian population sample: discrete and regression–based norms - Damasceno,Alfredo (2018)
ABSTRACT Objective Cognitive dysfunction is common in multiple sclerosis. The Brief Repeatable Battery of Neuropsychological Tests (BRB–N) was developed to assess cognitive functions most–frequently impaired in multiple sclerosis. However, normative values are lacking in Brazil. Therefore, we aimed to provide continuous and discrete normative values for the BRB–N in a Brazilian population sample. Methods We recruited 285 healthy individuals from the community at 10 Brazilian sites and applied the BRB–N version A in 237 participants and version B in 48 participants. Continuous norms were calculated with multiple–regression analysis. Results Mean raw scores and the 5th percentile for each neuropsychological measure are provided, stratified by age and educational level. Healthy participants' raw scores were converted to scaled scores, which were regressed on age, sex and education, yielding equations that can be used to calculate predicted scores. Conclusion Our normative data allow a more widespread use of the BRB–N in clinical practice and research.